New Zealand's Economic Growth - David Galt (New Zealand Government, The Treasury, 2000)
This paper forms part of the Treasury's ongoing work programme investigating New Zealand's economic performance. It represents one approach to understanding New Zealand's economic performance, that of reviewing theoretical and empirical literature on economic growth. Other research approaches the Treasury is adopting to shed light on these issues include: - monitoring New Zealand's total factor productivity performance; - learning from overseas experience; and reviewing linkages between specific policy issues and economic growth. The paper seeks to provide a synthesis of recent thinking about New Zealand's economic growth performance by reviewing international growth literature, and the views of commentators analysing New Zealand's economic performance. The synthesis suggests that there are no obvious policy options that will dramatically improve New Zealand's growth performance, and this is consistent with international findings on the growth experience of industrialised economies. Growth is influenced by much more than Government policy, even if well formulated. Current policy settings seem broadly consistent with the literature's general conclusions on requirements for growth. An important conclusion is that there are many potential contributors to growth. Typically, a small proportion of firms and industries contribute disproportionately to growth. The contribution of individual firms and sectors can change quite rapidly. Policy formation needs to take such a vision into account.
Keywords: 330